2015
DOI: 10.5352/jls.2015.25.7.795
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Hydrolysis Using Oyster and Oyster Cooking Drip

Abstract: Oyster is a nutritionally good food ingredient. Also, oyster is used to make source for taste and flavor. This study tried to investigate optimal condition of hydrolysis of oyster and oyster cooking drip for better amino acid content to make good taste and flavor. And then this study characterized hydrolysate of oyster and oyster cooking drip. Enzymes are Acalase, Flavourzyme, Neutrase, and Protamax. The optimal condition for the highest enzyme activity is given by the company. Under the best condition of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For example, the initial pH of yeast protein (about 7.09) rapidly decreased within 1 h, and the pH variations became less significant over time, which is generally observed during protein hydrolysis, suggesting that rapid degradation within a short period may exert a positive industrial impact on peptide production ( Suh et al, 2017 ). This decrease may be attributed by the protein degradation, leading to the accumulation of acidic AAs or the subsequently formed carboxyl groups ( Gam et al, 2019 ; Ryu et al, 2015 ). Thus, the proteolysis of yeast protein might positively affect the final protein qualities, however be differently affected by the enzyme types.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the initial pH of yeast protein (about 7.09) rapidly decreased within 1 h, and the pH variations became less significant over time, which is generally observed during protein hydrolysis, suggesting that rapid degradation within a short period may exert a positive industrial impact on peptide production ( Suh et al, 2017 ). This decrease may be attributed by the protein degradation, leading to the accumulation of acidic AAs or the subsequently formed carboxyl groups ( Gam et al, 2019 ; Ryu et al, 2015 ). Thus, the proteolysis of yeast protein might positively affect the final protein qualities, however be differently affected by the enzyme types.…”
Section: Resultsmentioning
confidence: 99%
“…OBC is rich in glycogen and free amino acids. OBC has a higher mineral content than raw oysters (Ryu et al., 2015) and a higher content of free amino acids, such as taurine, proline, glycine, alanine, and β‐alanine than fermented oyster solution (Jeong et al., 2017a). It has been found that about 80% of the total amino acid content of oysters is taurine (Hosoi et al., 2003; Jeong et al., 2017b).…”
Section: Introductionmentioning
confidence: 99%